KNOWLEDGE AND ATTITUDES OF EPILEPSY DISORDER AMONG UNDERGRADUATE HEALTHCARE PROFESSIONAL STUDENTS AT UNIVERSITY OF KUFA - Kadhim, Jihad Jawad; Tauma, Rusul Jabbar; Al-Fatlawi, Ammar Mahmood (International Journal Multidisciplinary (IJMI), 2026)
Objective: The association of epilepsy with possession of spirits is common in Iraqi society, leading to the stigmatization of people with epilepsy for generations. Closing the knowledge gap of university students and improving their attitude is key to alleviating this stigma. Method: Researchers created a self-administered questionnaire that examined medical students' knowledge of epilepsy and their attitudes towards it. We obtained epilepsy knowledge scores and examined their association with gender and college specializations. Results: The results showed that among 120 students, 83% had good knowledge of epilepsy, and 17% of them had low knowledge. Some of the students distinguished epilepsy as a hereditary disease, 34.2%. They identified loss of consciousness, behavior change and memory disturbance as signs of epilepsy, 57.5%, and 70.8% of them thought that symptoms of seizures include falling to the ground and foaming at the mouth. Novelty: This study showed that students of the medical group from the University of Kufa have a relatively better understanding of positive attitudes towards certain aspects of epilepsy; however, there are misconceptions they have in different aspects.